The South African Library as a state-aided national library in the era of apartheid : an administrative history - Coates, Peter Ralph (Department of Historical Studies, 2016)
The Public Library in Cape Town was founded in the earliest days of British civil rule in Southern Africa, as a Government-funded free library of reference with the purpose of educating and enculturating the 'youth' of the Cape Colony along European (especially English) lines. Government funding being withdrawn in 1829, the Library became an autonomous subscription library while continuing to provide access to its reference collections free of charge. During the ensuing 125 years the Library (known as the South African (Public) Library) becameincreasingly dependenton Government financial aid to provide certain 'national' functions. By 1954 it was the pre-eminent research library in sub-Saharan Africa and enjoyed total autonomy within the limits of its 1893 Act of the former Cape Colonial Parliament. This study follows the transformation of the South African Library into a Stateaided national library after it had divested itself of its local circulating services in 1955 and its subsequent existence with limited autonomy and increasing financial difficulties. During the transformation process, the National Party came into office in 1948 and introduced its authoritarian, centralizing style of administration. Many of the new Government's policies conflicted with the ethos and practices of the South African Library, particularly the promotion ofWhite Afrikaner culture in the place of the Library's generally White Anglophile culture, and the implementation of racial policies in the place of the Library's non-racialism. By the time the implications of National Party 'apartheid' policies became evident, it was too late for the Library to revert to its previous state. The scope of this administrative history of the Library in this era is limited to an analysis of themes which illuminate the relationship between the State, the Library, the Library's users, and the library profession at large during the development and eventual downfall in 1994 of National Party rule. The central themes are the Library's struggle to retain maximum professional autonomy in the context of its almost total dependence upon the State for its funding; the degree of State funding being determined by Government's perception of the Library's legitimacy and contribution to its policy priorities. Despite providing distinguished services to research (both formal and informal), especially in the humanities, and having perhaps the best collection in the country of published and manuscript material relating to Southern Africa, the South African Library was unable to attract the funding needed to sustain its rapidly growing collections and overwhelming amount of use. When the National Party left office in 1994, the Library was already on the point of financial collapse, and the incoming African National Congress Government had more pressing priorities. The South African Library failed, and in 1999, together with the State Library in Pretoria (which was itself in difficulties), became part of the National Library of South Africa in a development which, fifteen years later, must still be considered a compromise. Since the author considers the two-site compromise to be unsustainable, the study concludes with a review of various proposals which were put forward by library professionals between 1955 and 1994 which may profitably be revisited. The research was based on documentary records in the extensive administrative archive of the South African Library. This has been supplemented from published sources and recollections of the author and former colleagues.